2011
DOI: 10.1021/op100338z
|View full text |Cite
|
Sign up to set email alerts
|

Fast Scale-Up Using Microreactors: Pyrrole Synthesis from Micro to Production Scale

Abstract: A flow chemistry method for the synthesis of pyrroles was developed. The method was optimized in 0.13 to 7 μL microreactors in continuous flow, reaching yields of nearly 100%. Subsequently, the method was scaled up in continuous flow using a 9.6-mL internal volume, glass, microstructured flow reactor, leading to production of a pyrrole derivative at a rate of 55.8 g per hour .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
0
33
0
2
Order By: Relevance
“…30 Previous mechanistic studies have shown the rate determining step to be the cyclization step and for that reason the reaction was assumed to follow a single step mechanism with an unknown pre-exponential parameter (A), temperature dependence term ('activation energy') (E) and reaction orders (m,n).…”
Section: Analysis Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Previous mechanistic studies have shown the rate determining step to be the cyclization step and for that reason the reaction was assumed to follow a single step mechanism with an unknown pre-exponential parameter (A), temperature dependence term ('activation energy') (E) and reaction orders (m,n).…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…[6][7][8][9][10][11] Continuous flow systems have been used for complex chemical synthesis, [12][13][14][15] gas-phase reactions, [16][17][18][19] photochemistry, [20][21][22][23] electrochemistry, 24,25 and reaction optimization [26][27][28] but their robustness for reaction kinetics is hindered by the need to take steady state measurements. [29][30][31][32] Recent studies have shown that transient flow data could be used to quickly generate kinetic data. [33][34][35][36] Mozharov used the transient data generated from a step change in flow to scan different reaction times and fit kinetic data collected with inline Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The gram-scale flow synthesis of 2,5-dimethyl-pyrroles (35) from 2,5-hexanedione (36) was achieved by D-optimal algorithms aimed at defining the best set for temperature, stoichiometry of amine-diketone, and reaction time (Scheme 10) [28]. Two solutions of 36 and ethanolamine (37)-ethylamine (38) in MeOH were used as feedstock, and 2-bromotoluene was added as internal standard to follow the conversion of both the substrate and yield by quantitative GC-flame ionization detection (FID) analysis.…”
Section: Central Composite Designmentioning
confidence: 99%
“…We conducted the synthesis of pyrrole by reacting 2,5-hexanedione (Sigma) with ethanolamine (Sigma) in microdroplets on the chip (see Figure 6) [72]. We generated droplets from a compound stream formed by two incoming solutions of the substrates delivered directly into a FF-junction (SI, Figure S3).…”
Section: Chemical Reactions In Dropletsmentioning
confidence: 99%